Role of Recombinant DNA Technology in Transforming Human Life: A Review - Moses Kelas, Kario; Maikudi Usman , Mohammed; Sa’ad , Sani; Aisami, Abubakar (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
Recombinant DNA technology has revolutionized various aspects of human life, significantly impacting health, agriculture, and environmental sustainability. By enabling the manipulation of DNA from different species, this technology facilitates the production of essential proteins like insulin and growth hormones, enhancing medical treatments for chronic diseases. In agriculture, it promotes the development of genetically modified organisms that exhibit increased resistance to pests and improved crop yields, addressing food security challenges. Furthermore, recombinant DNA techniques are crucial in bioremediation efforts and gene therapy applications, highlighting their multidisciplinary relevance in contemporary society.